2016
DOI: 10.1210/en.2015-2046
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor-β (TRβ) Mediates Runt-Related Transcription Factor 2 (Runx2) Expression in Thyroid Cancer Cells: A Novel Signaling Pathway in Thyroid Cancer

Abstract: Dysregulation of the thyroid hormone receptor (TR)β is common in human cancers. Restoration of functional TRβ delays tumor progression in models of thyroid and breast cancers implicating TRβ as a tumor suppressor. Conversely, aberrant expression of the runt-related transcription factor 2 (Runx2) is established in the progression and metastasis of thyroid, breast, and other cancers. Silencing of Runx2 diminishes tumor invasive characteristics. With TRβ as a tumor suppressor and Runx2 as a tumor promoter, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 72 publications
5
31
0
Order By: Relevance
“…Additionally, RUNX2 was enriched in the GO BP terms ‘positive regulation of cell proliferation’ and in the KEGG pathway ‘transcriptional misregulation in cancer’. In agreement with this, previous studies have identified an association between the expression of RUNX2 and thyroid cancer progression ( 36 39 ). Therefore, RUNX2 may play an important role in thyroid tumorigenesis.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, RUNX2 was enriched in the GO BP terms ‘positive regulation of cell proliferation’ and in the KEGG pathway ‘transcriptional misregulation in cancer’. In agreement with this, previous studies have identified an association between the expression of RUNX2 and thyroid cancer progression ( 36 39 ). Therefore, RUNX2 may play an important role in thyroid tumorigenesis.…”
Section: Discussionsupporting
confidence: 88%
“…These factors include members of the nuclear hormone receptor family including estrogen, androgen, and thyroid hormone receptors (11)(12)(13). Our work has demonstrated that thyroid hormone receptor beta (TRβ) acts as a tumor suppressor in ATC through repression of several pathways important for tumor growth (14,15). However, the potential for TRβ to exhibit tumor suppression in ATC by suppressing PI3K is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Some TCs have favorable prognosis, however, aggressive TCs, which were characterized by a less differentiated cellular phenotype and a higher rate of metastasis and cancer-related mortality, have had no effective treatment approach [ 3 ]. While the development and progression of TCs are not completely clear, many genetic factors involved in their onset have been reported [ 4 8 ]. Increasing evidence has revealed the involvement of microRNAs (miRNAs) in human malignancies, and a number of important direct miRNAs-mRNAs regulations have been described in TCs [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%